The role of waqf investment funds in community development and helping the needy = دور الصناديق الاستثمارية الوقفية في تنمية المجتمع ومساعدة المحتاجين - Abulatifa, Mohammed; Mohd Noor, Azman; Hasan Saleh, Abdulmajid Obaid (2022)
The research aims to clarify the role of waqf investment funds in the development of societies and their contribution to the eradication of poverty. The researcher used the descriptive approach in describing and analyzing the phenomenon to reach the results reached by the researcher, including that endowment investment funds play a major role in the development of society, It also contributes to the eradication of poverty through economic empowerment programs and project financing. The researcher recommended the necessity of working on the development and preservation of endowment funds and the perpetuation of their benefits, due to their permanence in supporting and developing society in various fields. It is recommended that governments should adopt the idea of establishing waqf funds because they have a major role in reducing the government's obligations, lifting the burden on it, and supporting its strategic plan.